Hyperparathyroidism Associated with Long‐Term Proton Pump Inhibitors Independent of Concurrent Bisphosphonate Therapy in Elderly Adults. Issue 10 (29th September 2015) - Hinson, Andrew M.; Wilkerson, Bekka M.; Rothman‐Fitts, Ivy; Riggs, Ann T.; Stack, Brendan C.; Bodenner, Donald L.
<x xml:space="preserve">Abstract</x> Objectives To measure the effect of proton pump inhibitors (PPIs), with and without concurrent bisphosphonates, on parathyroid hormone (PTH), vitamin D, and calcium. Design Retrospective chart review of individuals 60 years and older. Subjects with reduced renal function (creatinine >1.3 mg/dL) and low vitamin D (<30 ng/mL) were excluded. Setting Academic geriatric outpatient center in southern midwest. Participants Individuals aged 60 and older with concurrent calcium, PTH, vitamin D, and creatinine laboratory measurements (N = 80) meeting labeled criteria. Measurements Serum calcium, PTH, vitamin D, and creatinine. Results Chronic PPI exposure was associated with statistically significantly higher PTH (65.5 vs 30.3 pg/mL, P < .001; normal range 10–55 pg/mL) and lower calcium (9.1 vs 9.4 mg/dL, P = .02; normal range 8.5–10.5 mg/dL) than no PPI exposure. Chronic PPI exposure with concurrent BP therapy was associated with statistically significantly higher PTH (65.2 vs 43.4 pg/mL, P = .05) and lower calcium (9.2 vs 9.6 mg/dL, P = .04) than BP therapy only. Conclusion Based on the present study, chronic PPI exposure in elderly adults is associated with mild hyperparathyroidism regardless of concurrent oral BP administration.